Scanning spreading resistance microscopy for electrical characterization of diamond interfacial layers. Issue 11 (14th July 2015) - Xu, Zheng; Hantschel, T.; Tsigkourakos, M.; Vandervorst, W.
Abstract : This paper presents a methodology to directly investigate on the nanometer scale electrical properties of the nucleation layer of grown diamond films, which are important when the film is used as an electrode with the current flow across the nucleation layer. The diamond films are grown on Si substrates. In this methodology, the Si substrate is locally removed by wet etching and electrical measurements are then carried out by scanning spreading resistance microscopy (SSRM). SSRM is based on atomic force microscopy (AFM) and measures the local spreading resistance underneath a conducting tip which is scanned in contact mode across the sample surface. Our work shows how SSRM can be applied on the diamond interfacial layer and what insights can be gained from these measurements. We show how undoped and boron‐doped seeds are incorporated at the interface and how the seed solution concentration impacts the interfacial seed density and the resulting interfacial electrical resistance. This paper discusses in more detail the sample preparation and measurement procedures.